Hybrid anion exchange membranes with self‐assembled ionic channels. Issue 6 (24th April 2017) - Liang, Na; Tu, Yufei; Xu, Jing; Chen, Dongzhi; Zhang, Hongwei
Abstract: A novel strategy for fabricating nanocomposite anion exchange membranes (AEM), which can construct self‐assembled ionic channels via in situ Menshutkin reaction, is proposed. The TEM image of a nanocomposite AEM based on chloromethylated polysulfone (CMPSF) and functionalized polyhedral oligomeric silsesquioxane (POSS) confirms the existence of core‐shell clusters. The ionic conductivity of these nanocomposite AEMs shows a notable increase when the content of functionalized POSS exceeds the percolation threshold. Furthermore, the optimized nanocomposite AEM has higher ionic conductivity than the control AEM with similar ion‐exchange capacity due to the well‐developed morphology.